E-094 Isolated intraventricular hemorrhage associated with cerebral vasospasm and delayed cerebral ischemia following arteriovenous malformation rupture. (22nd July 2018) - Al-Mufti, F; Amuluru, K; Majmundar, N; El-Ghanem, M; Patel, V; Romero, C; Gandhi, C
Abstract : Introduction: Although well characterized in aneurysmal subarachnoid hemorrhage, vasospasm is exceedingly rare following cerebral arteriovenous malformation (AVM) rupture. Subsequently, this complication is poorly characterized in regards to delayed cerebral ischemia (DCI). We review cases of ruptured AVMs to assess the frequency and severity of vasospasm on cerebral angiography, and DCI. Methods: We reviewed our institutional database of acute intracranial hemorrhages between 2005 and 2014, and identified patients with cerebral AVM rupture and evidence of vasospasm confirmed with digital subtraction angiography (DSA) were included. Cerebral angiograms were evaluated by 2 blinded neurointerventionalists for vasospasm. Statistical analyses were conducted on the angiographic results and variables of interest to determine predictors and associations of vasospasm and DCI. Results: Thirty-six patients with acute intracranial hemorrhage due to ruptured cerebral AVMs subsequently underwent cerebral angiography. The inter-rater reliability for vasospasm was 0.81. The incidence of vasospasm was 13.9% and the incidence of subsequent DCI was 11.1%. A significant relationship existed between isolated intraventricular hemorrhage and vasospasm (p=0.001) and subsequent DCI (p=0.006). Intraparenchymal hemorrhage was also associated with vasospasm (p=0.003) and subsequent DCI (p=0.001). Radiographic vasospasm was associated with DCI in 80% of patients (p<0.0001). No statistical significance existed between subarachnoid hemorrhage and the development of vasospasm or DCI (p=1.000 and p=0.626 respectively). All differences were significant at a 99% level of significance. Conclusion: In cases of ruptured AVMs, isolated intraventricular hemorrhage and intraparenchymal hemorrhage appear to be independent risk factors for vasospasm and DCI. Vasospasm must be considered during late neurological deterioration following AVM hemorrhage, especially in the setting of isolated IVH. Disclosures: F. Al-Mufti: None. K. Amuluru: None. N. Majmundar: None. M. El-Ghanem: None. V. Patel: None. C. Romero: None. C. Gandhi: None.